1997
DOI: 10.1093/toxsci/35.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Altered Hepatic Foci by 2,3′,4,4′,5-Pentachlorobiphenyl in Sprague-Dawley Female Rats

Abstract: The tumor promotion potential of 2,3',4,4',5-pentachlorobiphenyl (PCB-118) was studied in a two-stage initiation/promotion bioassay in female Sprague-Dawley rats. The animals were initiated by intraperitoneal administration of iV-nitrosodiethylamine after partial hepatectomy. After 5 weeks of recovery, the promotion period commenced by once-weekly subcutaneous administrations of PCB-118 at six dose levels (10, 40, 160, 640, 2500, and 10,000 /ig/kg body weight/week) for 20 weeks. In addition, three of these dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Based on studies with chicken embryos, it has been concluded that birds can be highly responsive toward non-ortho PCBs, although much of the information available concerns induction of CYPlAI and not distinct toxic (118) New data support the original value (91,96,108); no revision is recommended. 0.0001 0.0001 2',3,4,4',5-PentaCB (123) No new data are available; no revision is recommended.…”
Section: Tefs For Birdsmentioning
confidence: 99%
“…Based on studies with chicken embryos, it has been concluded that birds can be highly responsive toward non-ortho PCBs, although much of the information available concerns induction of CYPlAI and not distinct toxic (118) New data support the original value (91,96,108); no revision is recommended. 0.0001 0.0001 2',3,4,4',5-PentaCB (123) No new data are available; no revision is recommended.…”
Section: Tefs For Birdsmentioning
confidence: 99%
“…Tumour promotion experiments have shown that after initiation with a genotoxic carcinogen, technical PCB mixtures and individual dioxin-like and non dioxin-like congeners as well as TCDD act as liver tumour promoters in rats (Anderson et al, 1986;Buchmann et al, 1986;1990;Hemming et al, 1993;Haag-Grönlund et al, 1997;Dean et al, 2002). The promoting activity of di-ortho PCB such as PCB 47, 52, 49, and 153 has been demonstrated in short-term assays in which orally administered congeners promoted development of preneoplastic lesions in rat liver following induction by various initiators (Hemming et al, 1993;Preston et al, 1985).…”
Section: Carcinogenicitymentioning
confidence: 99%